Integration of life skills and HIV/AIDS into the South African schools' life orientation curriculum creating a model for NGO’s’ - Jennings, Marianne Angelique (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.